Interior of the garden greenhouse at Schönbrunn - Piringer, Benedikt, 1780-1826 (engraver):::Creator::::::::::::; Janscha, Laurenz, 1749-1812 (artist) ; Laborde, Alexandre Louis Joseph de, 1774-1842 (author):::Contributor:::::::::::: (Paris; France; Didot)
Aqautint image of the interior of the garden greenhouse at Schönbrunn